Pelatihan Optimalisasi Resiliensi Mengajar Guru Sekolah Dasar dengan Strategi Modifikasi Perilaku Prososial di Kecamatan Kalipare Kabupaten Malang - Ika Andrini Farida; Hanggara Budi Utomo; Raissa Dwifandra Putri; Syabiilah Azzahroh Widyatmoko Putri; Muhammad Aldwin Priyatama (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The current disruptive era provides challenges for teachers to innovate so that it has an impact on the level of stress experienced by teachers. Prosocial behavior modification support needs to be provided so that teachers can become resilient. The purpose of this service is to explore the effectiveness of prosocial behavior modification to increase teaching resilience in schools. The location of the service activities at SDN 1 Tempurejo, Malang Regency. The service partners are elementary school teachers who are members of the KKG Gugus 7 Kalipare District, Malang Regency, totaling 48 people. The method used is Participatory Action Research and data analysis using t-test. The results of community service activities are the increased understanding of elementary school teachers' knowledge about how to apply prosocial behavior modification strategies to optimize teaching resilience. The results of the understanding of teacher resilience also showed an increase after the implementation of education and socialization conceptualized in the form of seminars. The implication of this activity is that the knowledge that has been obtained by elementary school teachers can be applied sustainably in overcoming various problems that arise in their daily work